“Coming In” to Queer Psychology: The Value of Blending Queer Theory and Psychology in Critical Autoethnography - Wright, Alicia; Joy, Phillip; Barker, Conor (Atlantis)

(untitled) (Mount Saint Vincent University, 2025)
This commentary reflects upon an Honours thesis undertaken in 2024-2025 to analyze the subjective experience of coming out in adulthood through critical autoethnography. The method used, which blends autobiography with ethnographic observation, was rooted in psychological frameworks and drew upon queer theory—a scholarly perspective that challenges and attempts to disrupt heteronormative assumptions of gender and sexuality—to analyze the first author’s experience of changes in sexual orientation in her thirties. The authors discuss the challenges, and ultimate benefit, of interweaving psychology, which tends to be grounded in positivist and structured views, with queer theory, which promotes fluidity and resists established norms. Sharing their unique perspectives, each author contributed to this essay from their respective discipline, highlighting the possibilities that appear when holding two seemingly opposing theoretical tensions; not just in understanding experiences of diversity among sexual orientation identities, but also in questioning the traditional boundaries of research and the complexity of human experience. As researchers who are also part of the queer community, the authors found great value in queering psychology scholarship, supporting a need for diverse representation within academia.